Strategi Penguatan Ekonomi Lokal Berbahan Baku Ikan Bawis Menggunakan Bauran Pemasaran di Kelurahan Bontang Kuala Kecamatan Bontang Utara Kota Bontang - Zaid Taqiyyuddin; Badruddin Nasir (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Bontang Kuala, a coastal village in Bontang City, possesses abundant marine resources, particularly bawis fish (Siganus canaliculatus). However, this potential has not been fully optimized to strengthen the local economy. This study aims to examine strategies for strengthening the local economy through the management of bawis fish products using the 4P marketing mix (product, price, place, and promotion). This research employs a qualitative descriptive approach with data collection methods including observation, in-depth interviews with business owners and visitors, and field documentation. The findings indicate that business actors in Bontang Kuala have developed various processed bawis fish products, such as gammi bawis and dried bawis fish, marketed with pricing strategies adjusted to purchasing power. Most businesses are strategically located along the culinary tourism route, although accessibility challenges persist. Promotion strategies remain simple and limited to social media and local community support. Key supporting factors include raw material availability, high market demand, and community institutional support, while constraints include infrastructure limitations, suboptimal promotion, and raw material fluctuations. Overall, the management of bawis fish products has positively impacted community income and strengthened local economic identity. Recommendations include strengthening business infrastructure, enhancing digital promotion capacity, developing community-based business institutions, and expanding strategic partnerships among local actors.